2005
DOI: 10.1021/jo051729z
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of HIV-1 V3 Glycopeptides Carrying Two N-Glycans and Effects of Glycosylation on the Peptide Domain

Abstract: [structure: see text] A highly efficient chemoenzymatic synthesis of HIV-1 V3 domain glycopeptides carrying two N-linked core tri- and pentasaccharides was achieved. The synthesis consisted of two key steps: a solid-phase synthesis of the cyclic, 47-mer V3 domain peptide containing two GlcNAc residues and a novel endoglycosidase-catalyzed transglycosylation that simultaneously added two N-glycan moieties to the peptide precursor from the oligosaccharide oxazoline donor substrates. The availability of the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 42 publications
0
69
0
Order By: Relevance
“…65 The synthesis was achieved by a concise, two-step approach. First, the 47-mer polypeptide that contains two GlcpNAc moieties was prepared by an Fmoc-based solidphase peptide synthesis, using GlcpNAc-Asn as building blocks to introduce the two GlcpNAc tags.…”
Section: Exploring Transition State Analog Substrates For Endoglycosimentioning
confidence: 99%
“…65 The synthesis was achieved by a concise, two-step approach. First, the 47-mer polypeptide that contains two GlcpNAc moieties was prepared by an Fmoc-based solidphase peptide synthesis, using GlcpNAc-Asn as building blocks to introduce the two GlcpNAc tags.…”
Section: Exploring Transition State Analog Substrates For Endoglycosimentioning
confidence: 99%
“…[24] Seminal work in the field by Shoda and co-workers demonstrated that carbohydrate oxazolines are useful activated glycosyl donors for these enzymes, presumably since they mimic the putative oxazolinium ions which are intermediates in the enzymatic catalysed hydrolysis reaction. [25] Indeed the efficient synthesis of a series of glycopeptides has been achieved by transglycosylation with Endo A, [26,27] and investigations of a correlation of the efficiency of glycosylation with substrate structure have also been reported. [28] More recent work has also reported the application of the glycoprotein remodelling strategy using Endo A to access single glycoforms of ribonuclease B.…”
Section: Introductionmentioning
confidence: 99%
“…Immune escape of the virus from T-cell recognition by point mutation of targeted epitopes may have contributed to the decline seen in these patients. However, escape from T-cell recognition is thought to be most pronounced during the acute and early phases of infection and may subside over the course of simian immunodeficiency virus and HIV infections (5,23,27,29). Most importantly, high plasma loads and low CD4 cell counts at baseline predicted the loss of subdominant Gag responses.…”
Section: Discussionmentioning
confidence: 99%